البنية الفنية للرسائل النثرية المتبادلة بين الشريف الرضي وأبي إسحق الصابي - إبراهيم، خليل عبدالسادة; مجيد، حيدر عبدالجبار (مجلة اللغة العربية وآدابها, 2015)
This chapter deals the study of the art setup for reciprocal proe letters between Al_Shareef Al Radhy And Al _Sabyand it explainsthe display method of the tow writers in their sentimentality ,mentals subjects when reliance the artistic formula to technique structural by the overture , departure and concluding , also the other particularties is nominal from feachurs of the missives in AL Abbasside Era.